Comprehensive investigation of HBV-related hepatocellular carcinoma and choice of anti-HBV therapy - Huihui Lu; Wei Yi; Fangfang Sun; Zhan Zeng; Lu Zhang; Minghui Li; Yao Xie (Elsevier, 2021)
Chronic hepatitis B virus (HBV) infection is a global public health problem, which can cause chronic hepatitis, liver cirrhosis, hepatocellular carcinoma (HCC), and other diseases. Antiviral therapy is the most critical measure to slow down the progression of chronic hepatitis B, prevent or delay cirrhosis, HCC, and other kinds of liver decompensation events. At present, the anti-hepatitis B virus drugs are mainly nucleoside (acid) analogues (NAs) and interferon. Each kind of antiviral drug has different effects on the clinical outcome of hepatitis B patients (such as HCC). In this paper, we discussed the biological characteristics, natural course and prognosis of HBV infection, the mechanism of HBV-related HCC, the effect of different antiviral drugs on patients' outcome, predictive biomarkers and model for HBV clinical outcome, predictors of sustained response and recurrence after withdrawal of antiviral therapy, consideration of expanding therapeutic indications and antiviral therapy, hoping to give a hand to the clinical diagnosis and treatment of HBV.